Affinity and Influence of Federico García Lorca on the Poetry of Dai Wangshu - Jiajing, Song (Sinología hispánica. China Studies Review, 2019)
As one of the most representative modern poets in China, Dai Wangshu not only contributs a lot to the development of the modern Chinese poetry, but also plays an important role in introducing western poetics to China. Dai’s translation of western poetry has a profound influence on his poetic creation. Dai, throughout his poetic career, was at first influenced by the French romanticism, then was fascinated by the French symbolism and post-symbolism. The years of Disaster, a collection of poems in his later years, however, demonstrates an inclination to the Spanish modernist poetry, especially to the poems of Federico García Lorca, one of the most representative poets of the Generation of 27. This paper focuses on analyzing the characteristics of the works of these two poets, Dai Wangshu and Lorca, and is intended to make a comparative study of the affinities and similarities in their poetic beliefs and practice and the Lorca’s deep influences on Dai’s poetic creation, thus filling the blank in this field.